Gastroblastoma: a case report and literature review - Li, Jiayu; Wang, Gang; Jiang, Zhiwei (Frontiers in Oncology, 2024)
Objective Gastroblastoma is an extremely rare gastric tumor. Its pathogenesis remains unclear and there is a lack of specific clinical symptoms. The aim of this paper is to report a case of gastroblastoma and provide references for the diagnosis, treatment, and prognosis of this disease. Methods The diagnosis and treatment of a 51-year-old female patient with gastroblastoma were retrospectively reported. Analyzing this case by combining the clinical data such as imaging and pathological results of patients with the relevant literature. Results The patient’s chief complaint was the presence of melena persisted for over two weeks. Abdominal contrast-enhanced CT showed gastric antral nodules, and micro-probe endoscopic ultrasonography was considered as “gastric antral protruding lesions”. The initial diagnosis of “gastric stromal tumor” was made after admission, and surgical treatment was performed on September 23, 2021. Postoperative pathology showed that gastric mixed epithelial and stromal tumor, combined with immunohistochemical staining, was suggestive of gastroblastoma. No signs of tumor recurrence or metastasis were observed during the 2-year follow-up. Conclusion Combined with the existing literature reports, the incidence of gastroblastoma is mainly higher in young men, and the predilection site is gastric antrum. The biological behavior of the tumor tends to be indolent, and the prognosis of most cases is favorable. However, due to the extremely small number of cases, this conclusion still needs a large number of cases and follow-up data to support. Postoperative pathological and immunohistochemical examination results are the only methods for definite diagnosis at present, and surgery is the first choice for treatment.